Data Dissemination and Use (DDU) Strategy Development: Design of the DDU Strategy Methodology - Darcy, Niamh M; Somi, Geoffrey; Matee, Mecky; Wengaa, Desderi; Perera, Sriyanjit (Journal of Health Informatics in Africa, 2017)
Many developing countries have included improving data use as part of their overall health sector strategy, usually included as part of their Monitoring and Evaluation (M&E) section. Tanzania decided to develop a more comprehensive data dissemination and use (DDU) strategy, based on primary research and secondary data review to understand the challenges and opportunities that exist to improve evidence-based decision-making at all levels of the health system. The results were used to develop the DDU strategy. This paper presents the methodology used to develop the DDU strategy.